RANCANG BANGUN MESIN PENGHALUS LADA (PIPER NIGRUM) DENGAN KEHALUSAN MINIMAL 50 MESH - Andreas Rizaldi (2024)
Pepper (Piper Nigrum L) is one of the spices with a very high selling value. Pepper has a small round shape that has a spicy, bitter and warm flavour. Therefore, pepper must be ground into powder in order to maintain the flavour image and soak into the food. The size of white pepper powder according to the Babel Agricultural Technology Assessment Centre (BPTP) is 50 to 60 mesh. In the process of grinding pepper, traditional methods are still widely used. This method uses a mortar or pestle to turn the pepper into a finer form. To overcome this limitation, pepper crushing machines are used. Although pepper crushing machines have made the process easier, there are still some challenges faced. Some of these include cost, machine capacity, and the quality of the grind. The results of the research obtained a pepper crushing machine with a fineness level of 50 mesh with a size of 550 x 400 mm and a height of 1055 mm with a capacity of 3.67 kg/hour with a machine productivity of 91.8%.